LEGAL SOCIOLOGY STUDY OF PREVENTION EFFORTS AND OVERCOMING DOMESTIC VIOLENCE (DOM) AGAINST WOMEN - Anton Liberto; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Indonesia is a country based on law, as enshrined in the 1945 Constitution. The concept of a state based on law states that the necessities of life within the state must be based on applicable legal rules in policy decision-making. According to Jimly Asshiddiqie, one of Indonesia's characteristics as a country based on law is the regulation of human rights. This regulation aims to protect humans from degrading their dignity. One form of degrading dignity is domestic violence (KDRT). Domestic violence, including physical, psychological, sexual, and economic violence, is a criminal act that occurs within a household where the perpetrator and victim are from the same household. The government has regulated sanctions for criminal acts of domestic violence in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This regulation demonstrates the government's attention to human rights, gender, non-discrimination, and protection. Victims of domestic violence. Although there is a law regulating domestic violence, cases of domestic violence continue to increase. The results of this study indicate that domestic violence occurs due to internal and external factors. In an effort to address the problem of domestic violence, the author provides two solutions using legal media and coordination between the community, social institutions, and law enforcement..